O „ukrytym” w prozie Michala Ajvaza i Piotra Pazińskiego - Firlej, Agata (Slavia Occidentalis, 2013)
In this essay I juxtapose the output of Michal Ajvaz and Piotr Paziński, analyzing it as a similar literary strategy for metaphorising the concept of the “re-start” in the history of culture. The starting point is a similar phenomenon in North American literature, described by Eliot Weinberger, who uses a (not explicitly declared) psychoanalytic methodology. Key references, in addition to the modernist inspiration, are also: the urban text, Talmudic imaging, the phenomenon of memory/palimpsest and the possibility or impossibility of the artistic representation of the Holocaust.